The Role of Non-Formal Education in Improving Early Childhood Life Skills - Ahmad Fadhil; Jamarusdi; Malkayanti S. Sangadji; Nur Ali; Ani Rindiani (STIT Attaqwa, 2025)
This study aims to examine the role of Non-Formal Education (NFE) in enhancing life skills among early childhood. The background is based on the importance of developing life skills as essential preparation for children to face future life challenges, while the formal education system has not been able to optimally meet these needs. The research method used is a literature review, involving the collection and analysis of various relevant sources such as books, journals, papers, and official documents. The findings indicate that NFE significantly contributes to the development of practical, social, emotional, and cognitive aspects of children through innovative learning approaches, hands-on experiences, and participatory methods. Through flexible and contextual programs and activities, NFE complements the strengths of formal education and supports the holistic growth and development of children. Therefore, collaboration among various stakeholders, including the government, educational institutions, families, and communities, is necessary to optimize the role of NFE in fostering life skills in early childhood. Thus, NFE can serve as an effective alternative in supporting character education and preparing children for a dynamic future.